Controle estatístico da qualidade na fertirrigação por gotejamento sob diferentes inclinações - Lopes, Allan Remor (2019)
For a drip fertigation system to function excellently, its uniformity must be high. The unifomirty evaluation of a drip fertigation system is based on the verification of flow, pressure, electrical conductivity, and pH. Uniformity is influenced by several factors, including terrain topography. For uniformity to be better monitored, it is important to use statistical techniques, such as statistical quality control, through Shewhart control charts, Exponentially Weighted Moving Average (EWMA), Cumulative Sum (CUSUM) and Zones, which enable its monitoring. Thus, the objective of this work was to evaluate the process of drip fertigation using statistical quality control. The work was divided into three articles, with the specific objectives of evaluating the influence of the system slope on drip irrigation flow uniformity; the uniformity of a drip fertigation system using monopotassium phosphate (MKP); and the influence of slope on the uniformity of a drip fertigation system using liquid peat. The tests were performed in the laboratory, using a bench, with less influence of external factors. Regarding the different slopes in drip irrigation, downslope irrigation was the most uniform; as for the level and upslope systems, the highest flows were observed at the beginning of the lines, while for the downslope the end of the line presented the highest flows. Zones control chart was highly sensitive when compared to CUSUM and Shewhart control charts. For the use of Monopotassium Phosphate (MKP) in fertigation, the use of MKP showed excellence in uniformity of flow, electrical conductivity, pH, and pressure. The level system was the most uniform, with the highest uniformity of all attributes analyzed. For flow uniformity, the control charts showed that the level system was under statistical control and the upslope and downslope systems were not. In all slopes the pressure uniformity was excellent with indices close to 100%. However, all control charts showed that the process was out of statistical control. The use of liquid peat showed that at all slopes, the drip flow increases and decreases throughout line, and the electrical conductivity throughout the line decreases at upslope and increases at downslope. Liquid peat on all slopes obtained excellent uniformity for all parameters evaluated. The CUSUM control chart was very sensitive in monitoring the uniformity of liquid peat when compared to the Shewhart control chart.